Innovación tecnológica en la elaboración de “FARINA” Fortificada - Chavéz Flores, Henry James (2003)
The cassava (Nanihoc escalenta Cr.antz) cultivates in the tropical world, placed in second of impot"tance, surpassed by potato, as a feculent root in tropic countries. Actually, it is cultivating widely as a food plant or industrial purposes. The present research work: was realízed wíth the objectíve of establishing technological parameters for processing of fortified "farífia" from fermented cassava (Jfanihot escalenta Crantz) variety Motelina Blanca, comprehended by two (2) defined steps: macerated and fermented pulp obtainment, and processing of fortified "farifia". The cassava root (Manihot esculenta Crantz) variety Motelina blanca, reported high content of carbohydrate (35.95%), protein (0.83%), fat (0.90%), fibre (0.94%), ash (1.11%) and (61.21%). moisture It contains 23.15% acidity, 4 .25 pH of grated and inoculated cassava pulp after its total softening time. The mixed mass with PROMINE DSP (powder, flavor very insipid and without odor) containing 63.4% protein, 2.36% moisture, 3.8% fibre, 1.01% ash, and with soy lecithin, liquid and 100% pure. The mixture is in a ratio 1 : 2 (PROMINE DSP : pressed mass) and 3.125% from pressed mass without difficulty to homogenize them. The toasted after mixed and transformed in fortified \'farifia" has reported the following composition: 22.021% pro te in, 59.259% carbohydrate, 4.08% fat, 2.12% fibre, 3.06% ash, 10.46% moisture, 0.097% acidity and 6.44 pH, and gave the same typical characteristics of pure "farifia" ready for consumption·1n breakfast. The optimum flux of processing was: cassava root, selected, washed-peeled, grated, macerated and fermented (by a selective inoculate of 3 mL), pres sed, si fted, mixed, to asted (130ºC), cooled, packed (high density polyethylene)) and stored (atmosphere temperature). The yielding of forti fied "farina" was 51. 52% starting cassava root. It presented microbiological characteristics very acceptable with a reduced microbial count, demonstrating strict hygiene conditions employed during processing about. The sensorial test of forti fied "farina" was rejected very significantly in attribute of flavor compared with non-fortified "farina", owing to a neutral taste but not confered a rare or disagreeable taste. With regard to sensorial test on acceptability level between a commercial product, were both widely accepted significantly by a target public on scholastic age.